Corona Pandemic Between Force Majeure And Unexpected Circumstanses - صالح , فواز; دكدوك, علاء (Tishreen University Journal- Economic and Legal Sciences Series, 2021)
After outbreaks of new coronavirus (COVID19) around the world, all the countries taken several actions to address this pandemic, which constitutes indisputably exceptional, general and unpredictable incidents. Accordingly, it is valid for all provisions of force majeure and unexpected circumstances, depending on the extent of its impact on contractual obligations in making commitments impossible or onerous. In this search showed provisions of force majeure and unexpected circumstances, and on the applicability of its terms for corona pandemic in Syrian civil law and new French law.